Introduction to probability models - Ross, Sheldon M. (Academic Press is an imprint of Elsevier, 2014)
This revised and updated text introduces readers to the application probability theory to phenomena in fields such as engineering, computer science, management and actuarial science, the physical and social sciences, and operations research. It contains exercises and worked examples.